The Heineke-Mikulicz Principle for Hepaticojejunostomy Stricture - Orhan Hayri Elbir; Kerem Karaman; Ali Surmelioglu; Erdal Birol Bostanci; Musa Akoglu (Case Reports in Surgery)
Benign anastomotic stricture after hepaticojejunostomy is one of the serious complications of biliary surgery. If left untreated, jaundice, cholangitis, or cirrhosis may develop. A 58-year-old male patient was admitted with benign hepaticojejunostomy stricture. The patient initially underwent an endoscopic retrograde cholangiography using double-balloon enteroscope, which was unsuccessful due to the sharp angle between the jejunal limb and the biliary tree. It was decided to perform surgery. During the operation, we performed Heineke-Mikulicz strictureplasty to the narrowed anastomosis. Patient’s postoperative course was uneventful. At the end of followup, for 18 months, his liver enzymes were within normal ranges, and the ultrasound examination showed a patent hepaticojejunostomy anastomosis. The simplicity of the technique and the promising result support the applicability of the Heineke-Mikulicz principle in suitable cases as an alternative treatment approach for hepaticojejunostomy strictures.